Enfermedades infecciosas y parasitarias presentes en Bovinos de la Provincia de Tungurahua. - Fraga Ayala, Juan Fernando (2017)
This researching project determines the prevalence of the main infectious and parasitic diseases in cattle in Tungurahua province through the review of cases reported in the OIE (World Organization for Animal Health) and coprology tests to establish epidemiological records. For this purpose, was collected data to determine the incidence of diseases related to the research project in the years between 2010 – 2015 years, in relation to infectious diseases. For the identification of gastrointestinal parasites, the study was carried out on cattle sampled in Tungurahua province which presented parasitic diseases. 200 cattle were estimated, each one was identified according to a clinical file; general background, name, age, sex, and date. Each sample was classified and the coprology tests were performed in each of them. The type of parasite egg was identified under the microscope and the different types of parasites found in the sampled animals were classified. In 2010, brucellosis had a higher prevalence with (0.053), followed by tuberculosis (0.013), while Bovine Enzootic Leukosis (EBL) and Bovine Infectious Rhinotracheitis (0.007) were the lowest prevalence. In 2011, Leptospirosis and Brucellosis (BrucellaAbortus) were the most prevalent diseases with (0.12), followed by Bovine Viral Diarrhea with (0.07), Bovine Infectious Rhinotracheitis (0.06), Enzootic Bovine Leukosis (0.05), and Bovine Tuberculosis Was the lowest prevalence with (0.02). In the year 2012, Bovine Viral Diarrhea, Enzootic Bovine Leukosis and Bovine Infectious Rhinotracheitis were the most prevalent diseases with (0.04), followed by Bovine Tuberculosis with (0.03), while Brucellosis (BrucellaAbortus) and Vesicular Stomatitis were the lowest prevalence with (0.007). In the year 2013 Bovine Viral Diarrhea was the most prevalent disease with (0.06), followed by Bovine Infectious Rhinotracheitis with (0.03), Enzootic Bovine Leukosis with (0.02), while the lowest prevalence was Brucellosis (BrucellaAbortus) with 0.07). In the year 2014 the most prevalent disease was Brucellosis with (0.09), followed by Bovine Viral Diarrhea and Bovine Infectious Rhinotracheitis with (0.05), and the disease with the lowest prevalence was enzootic Bovine Leukosis with (0.02). In the year 2015 the disease with the highest prevalence was Brucellosis with (0.15), followed by Bovine Infectious Rhinotracheitis with (0.03), Bovine Viral Diarrhea with (0.02), while the one with the lowest prevalence was enzootic Bovine Leucosis with (0.01). In the coprology analyzes were evidenced that in 42% of the sampled animals had the presence of Coocidia eggs, being the most prevalent etiological agent in Tungurahua province, followed by 32% with the presence of Oesophagostomum, 11% with Bunostomum presence, 5% with Haemonchus presence, 4% with Chabertia presence, 2% with Dictyocaulus and Cooperia, and the parasite eggs with lower prevalence were Trichuris and Ostertagia with 1%.